On the Complexity and Accuracy of Geographic Profiling Strategies - Snook, Brent (Journal of quantitative criminology, 2005)
Geographic profilers have access to a repertoire of strategies for predicting a serial offender’s home location. These strategies range in complexity—some involve more calculations to implement than others—and the assumption often made is that more complex strategies will outperform simpler strategies. In the present study, we tested the relationship between the complexity and accuracy of 11 strategies. Data were crime site and home locations of 16 UK residential burglars who had committed 10 or more crimes each. The results indicated that strategy complexity was not positively related to accuracy. This was also found to be the case across tasks that ranged in complexity (where complexity was determined by the number of crimes used to make a prediction). Implications for police’ policies and procedures, as well as our understanding of human decision-making, are discussed.